Kecemasan Masa Depan pada Mahasiswa Tingkat Akhir: Adakah Peranan Internal Locus of Control? - Putri, Marsella Aprilola Dwi; Matulessy, Andik; Pratitis, Nindia (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2024)
AbstractThe uncertainty of life in the future makes final year students feel worried about the failure experienced later in fulfilling existing tasks and demands so that this can trigger final year students to experience future anxiety. This study aims to determine the relationship between internal locus of control and future anxiety in final year students. This research is a type of quantitative research using correlational research. The subjects in this study were 321 final year students. The research instruments used the internal locus of control scale and the Future Anxiety Scale (FAS) adapted from Zaleski (1996). The data analysis technique used Spearman's Rho analysis technique with the help of the IBM Statistical Package for Social Science (SPSS) version 25 for windows program. The results showed a significant negative relationship between internal locus of control and future anxiety in final year students, meaning that the higher the internal locus of control, the lower the future anxiety of final year students. Conversely, the lower the internal locus of control, the higher the future anxiety of final year students.Keywords: Final Year Students; Future Anxiety; Internal Locus of Control AbstrakKetidakpastian kehidupan di masa depan membuat mahasiswa tingkat akhir merasa khawatir akan kegagalan yang dialami nantinya dalam memenuhi tugas dan tuntutan yang ada sehingga hal tersebut dapat memicu mahasiswa tingkat akhir mengalami kecemasan masa depan. Penelitian ini bertujuan untuk mengetahui hubungan antara internal locus of control dengan kecemasan masa depan pada mahasiswa tingkat akhir. Penelitian ini merupakan jenis penelitian kuantitatif dengan menggunakan penelitian korelasional. Subjek dalam penelitian ini sebanyak 321 mahasiswa tingkat akhir. Instrumen penelitian menggunakan skala internal locus of control dan The Future Anxiety Scale (FAS) yang diadaptasi dari Zaleski (1996). Teknik analisis data menggunakan teknik analisis Spearman’s Rho dengan bantuan program IBM Statistic Package for Social Science (SPSS) versi 25 for windows. Hasil penelitian menunjukan adanya hubungan negatif yang signifikan antara internal locus of control dengan kecemasan masa depan pada mahasiswa tingkat akhir, artinya semakin tinggi internal locus of control maka semakin rendah kecemasan masa depan mahasiswa tingkat akhir. Sebaliknya semakin rendah internal locus of control maka akan semakin tinggi kecemasan masa depan mahasiswa tingkat akhir.Kata kunci: Internal Locus of Control; Kecemasan Masa Depan; Mahasiswa Tingkat Akhir